2013
DOI: 10.1371/journal.pntd.0001931
|View full text |Cite
|
Sign up to set email alerts
|

O'nyong nyong Virus Molecular Determinants of Unique Vector Specificity Reside in Non-Structural Protein 3

Abstract: O'nyong nyong virus (ONNV) and Chikungunya virus (CHIKV) are two closely related alphaviruses with very different infection patterns in the mosquito, Anopheles gambiae. ONNV is the only alphavirus transmitted by anopheline mosquitoes, but specific molecular determinants of infection of this unique vector specificity remain unidentified. Fifteen distinct chimeric viruses were constructed to evaluate both structural and non-structural regions of the genome and infection patterns were determined through artificia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 38 publications
1
70
0
Order By: Relevance
“…Viable nsP chimeras have been generated for two closely related members of Semliki Forest complex, Chikungunya and O'nyongnyong viruses; however, nsP chimeras between members of different alphavirus complexes have not been reported, presumably due to nsP incompatibilities (71). Taken together, our data suggest that the electroporation of capped, genomic RNA of EILVeRFP, EILV-eRFP with SINV structural ORF, or 3= UTR chimeras can initiate the virus replication cycle by the translation of the nsP ORF.…”
Section: Fig 8 Predicted Secondary Structure Of Eilv (A) and Sinv (B) 3=mentioning
confidence: 80%
“…Viable nsP chimeras have been generated for two closely related members of Semliki Forest complex, Chikungunya and O'nyongnyong viruses; however, nsP chimeras between members of different alphavirus complexes have not been reported, presumably due to nsP incompatibilities (71). Taken together, our data suggest that the electroporation of capped, genomic RNA of EILVeRFP, EILV-eRFP with SINV structural ORF, or 3= UTR chimeras can initiate the virus replication cycle by the translation of the nsP ORF.…”
Section: Fig 8 Predicted Secondary Structure Of Eilv (A) and Sinv (B) 3=mentioning
confidence: 80%
“…Due to its rapid evolution, the HVD is hypothesized to be involved in the optimization of replication in diverse host cell types (51). Chimeric viruses containing CHIKV and o'nyong-nyong virus (ONNV) genes showed that, in the CHIKV backbone, the ONNV nsP3 gene confers the ability to infect Anopheles mosquitoes, natural vectors of this close relative of CHIKV (52). Another study suggested that deletion of the HVD of Sindbis virus causes it to be defective for mosquito cell infection (53).…”
Section: Discussionmentioning
confidence: 99%
“…Construction of the chimeras receiving material not bordered by these sites and the point chimeras was based on a strategy using type IIs restriction enzymes adapted from Blakqori and Weber [12] and is outlined in detail by Saxton-Shaw et al for the generation chikungunya/oâ€Čnyong nyong chimeric viruses [13]. This method allowed the generation of chimeras and point mutants without the introduction of nonnative nucleotides to the virus.…”
Section: Methodsmentioning
confidence: 99%